A Rare Case of Magnesium Alkyl Mediated CO-to-Alkoxide Conversion - Townrow, Oliver; Richter, Tim; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2024)
Alcohols can be produced by nucleophilic addition at the C=O functional group of ketones or aldehydes. Such C−C bond formations generally proceed smoothly and selective. In contrast, nucleophilic addition at carbon monoxide is considerably more complex and unselective due to the instability of polar metal acyl intermediates. Herein, we report a magnesium alkyl complex, stabilised with a dipyrromethenide ligand, and its reactivity with CO2 and CO. Whilst the reaction with CO2 gave the expected carboxylate, reaction with CO took a surprising course, resulting in an alkoxide by formation of three new C−C bonds in a single reaction. An intertwined experimental and computational approach sheds light on the unusual reactivity of a carbene intermediate.
CRIS-Team Scopus Importer:2024-11-29
Keywords: carbon monoxide; C−H activation; dipyrromethane; magnesium; metal alkyl